Annihilator Conditions Relative to a Class of Modules: Dexu Zhou, Demei Li, Lili Guo - Team, Support (Thai Journal of Mathematics, 2010)
Annihilator conditions relative to a class of modules are studied and used to characterize the relative extending modules. In particular, dual rings relative to the class of all small right ideals, called right small-dual rings, are investigated and some known results on the dual rings are generalized to the case of small-dual rings.